Kendala yang Dihadapi oleh Pemerintah Kabupaten Agam dalam Menjalankan Peran Mereka dalam Meningkatkan Kesiapsiagaan Menghadapi Ancaman Bencana Erupsi Gunung Marapi - Hayati A.S, Fadhla; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This research aims to determine the obstacles or obstacles faced by the Agam Regency Government in carrying out their role in increasing preparedness to face the threat of the Mount Marapi eruption disaster. This research uses a descriptive qualitative approach with data collection techniques using interview and documentation techniques. The research findings show that there are obstacles or obstacles faced by the Agam Regency Government in increasing its preparedness to face the threat of the Mount Marapi eruption disaster, namely internal obstacles and external obstacles.